Firm-level attitudes and actions to the "Twin Transition" challenges of digitalisation and climate change - Janez Kren; Martina Lawless (The Economic and Social Research Institute (ESRI), 2023)
Mitigating and adapting to climate change is a central global challenge that may incur costs for many businesses but also one that could bring opportunities in terms of productivity and new markets. Increased use of digital technologies is an area where the challenge of climate adaptation and promotion of productivity growth may be bridged. This research uses firm-level evidence from Ireland to examine firm attitudes and the determinants of firm participation in one or both of the "twin transition" elements. The data is drawn from a large-scale survey including novel questions on energy use, climate adaption priorities and digital strategies along with a wide range of firm characteristics. Larger and more productive firms are more likely to have higher degrees of digitalisation and to have climate action plans in place. Firm productivity is also positively linked to active steps such as measuring CO2 emissions. We find considerable overlap between having a climate and a digital plan in place across firms while controlling for a range of other firm characteristics. At the same time, we find a reasonably large share of firmsthat have positive attitudes to the importance of climate planning but without reporting corresponding concrete actions, suggesting a gap for policy to address.
Keywords: 330; Digitalisierung; Klimapolitik; Umweltmanagement; Unternehmen; Irland